Chitosan porous 3D scaffolds embedded with resolvin D1 to improve in vivo bone healing. Issue 6 (3rd March 2018) - Vasconcelos, Daniela P.; Costa, Madalena; Neves, Nuno; Teixeira, José H.; Vasconcelos, Daniel M.; Santos, Susana G.; Águas, Artur P.; Barbosa, Mário A.; Barbosa, Judite N.
Abstract: The aim of this study was to investigate the effect chitosan (Ch) porous 3D scaffolds embedded with resolvin D1 (RvD1), an endogenous pro‐resolving lipid mediator, on bone tissue healing. These scaffolds previous developed by us have demonstrated to have immunomodulatory properties namely in the modulation of the macrophage inflammatory phenotypic profile in an in vivo model of inflammation. Herein, results obtained in an in vivo rat femoral defect model demonstrated that two months after Ch + RvD1 scaffolds implantation, an increase in new bone formation, in bone trabecular thickness, and in collagen type I and Coll I/Coll III ratio were observed. These results suggest that Ch scaffolds embedded with RvD1 were able to lead to the formation of new bone with improvement of trabecular thickness. This study shows that the presence of RvD1 in the acute phase of the inflammatory response to the implanted biomaterial had a positive role in the subsequent bone tissue repair, thus demonstrating the importance of innovative approaches for the control of immune responses to biomedical implants in the design of advanced strategies for regenerative medicine. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1626–1633, 2018.